Monocrystalline NiS nanowire arrays supported by Ni foam as binder-free electrodes with outstanding performances. Issue 36 (25th April 2017) - Xu, Yali; Du, Weimin; Du, Lulu; Zhu, Wenjuan; Guo, Wei; Chang, Jingjing; Zhang, Bing; Deng, Dehua
Abstract : Monocrystalline NiS nanowire arrays can achieve a higher areal capacitance of 8.7 F cm −2 and excellent capacitance retention (78.7% after 8000 cycles). Abstract : Monocrystalline NiS nanowire arrays supported by Ni foam were synthesized without any surfactant. Characterization results reveal that the as-obtained NiS nanowires belong to a rhombohedral phase with higher aspect ratio. Electrochemical measurements indicate these nanowire arrays can achieve a higher areal capacitance of 8.7 F cm −2 at the current density of 20 mA cm −2, together with good rate capability and excellent cycling stability (78.7% capacitance retention after 8000 cycles).